Convergence Detection in Direct Simulation Monte Carlo Calculations for Steady State Flows (Communications in Computational Physics, 2011)
A new criterion is presented to detect global convergence to steady state,and to identify local transient characteristics, during rarefied gas flow simulations performedusing the direct simulation Monte Carlo (DSMC) method. Unlike deterministiccomputational fluid dynamics (CFD) schemes, DSMC is generally subject to large statisticalscatter in instantaneous flow property evaluations, which prevents the use ofresidual tracking procedures as are often employed in CFD simulations. However,reliable prediction of the time to reach steady state is necessary for initialization ofDSMC sampling operations. Techniques currently used in DSMC to identify steadystate convergence are usually insensitive to weak transient behavior in small regionsof relatively low density or recirculating flow. The proposed convergence criterion isdeveloped with the goal of properly identifying such weak transient behavior, whileadding negligible computational expense and allowing simple implementation in anyexisting DSMC code. Benefits of the proposed technique over existing convergencedetection methods are demonstrated for representative nozzle/plume expansion flow,hypersonic blunt body flow and driven cavity flow problems.